2023
DOI: 10.3390/life13020324
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Oral Human Herpesvirus-6 and -7 and Periodontal Conditions in Older Adults

Abstract: Background: The associations between oral human herpesvirus-6 (HHV-6) and HHV-7, periodontal conditions, and lifestyle-related diseases, such as hypertension, diabetes, and dyslipidemia, have not been fully investigated in older adults. Methods: Seventy-four older patients who visited Hiroshima University Hospital were enrolled. Tongue swab samples were employed, and a real-time polymerase chain reaction was performed to detect HHV-6 and HHV-7 DNA. Dental plaque accumulation, probing pocket depth, and bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[ 59 , 60 ]. In the oral cavity, it has been suggested that HHV-7 is associated with active periodontitis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 , 60 ]. In the oral cavity, it has been suggested that HHV-7 is associated with active periodontitis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that oral EBV has a prevalence rate of 20% and is associated with PISA and plaque control record scores (37). Additionally, oral human herpesvirus-7 is commonly found in individuals with deep periodontal pockets (38). However, the association between Capnocytophaga species and periodontal herpes virus remains unclear.…”
Section: Ochracea/c Sputigenamentioning
confidence: 99%
“…In fact, CMV seroprevalence was highest in South America, Africa, and Asia, and lowest in Western Europe [29]. Moreover, few studies have addressed the molecular identi cation of the herpesviruses after the updates of the new Classi cation of Periodontal and Peri-Implant Diseases [31,32], and to the authors knowledge, none have compared CMV and EBV occurrence in patients with periodontitis in the Spanish population.…”
Section: Introductionmentioning
confidence: 99%